High plasma concentrations of acyl‐coenzyme A binding protein (ACBP) predispose to cardiovascular disease: Evidence for a phylogenetically conserved proaging function of ACBP. Issue 1 (12th December 2022) - Montégut, Léa; Joseph, Adrien; Chen, Hui; Abdellatif, Mahmoud; Ruckenstuhl, Christoph; Motiño, Omar; Lambertucci, Flavia; Anagnostopoulos, Gerasimos; Lachkar, Sylvie; Dichtinger, Silvia; Maiuri, Maria Chiara; Goldwasser, François; et al.
Abstract: Autophagy defects accelerate aging, while stimulation of autophagy decelerates aging. Acyl‐coenzyme A binding protein (ACBP), which is encoded by a diazepam‐binding inhibitor (DBI), acts as an extracellular feedback regulator of autophagy. As shown here, knockout of the gene coding for the yeast orthologue of ACBP/DBI ( ACB1 ) improves chronological aging, and this effect is reversed by knockout of essential autophagy genes ( ATG5, ATG7 ) but less so by knockout of an essential mitophagy gene ( ATG32 ). In humans, ACBP/DBI levels independently correlate with body mass index (BMI) as well as with chronological age. In still‐healthy individuals, we find that high ACBP/DBI levels correlate with future cardiovascular events (such as heart surgery, myocardial infarction, and stroke), an association that is independent of BMI and chronological age, suggesting that ACBP/DBI is indeed a biomarker of "biological" aging. Concurringly, ACBP/DBI plasma concentrations correlate with established cardiovascular risk factors (fasting glucose levels, systolic blood pressure, total free cholesterol, triglycerides), but are inversely correlated with atheroprotective high‐density lipoprotein (HDL). In mice, neutralization of ACBP/DBI through a monoclonal antibody attenuates anthracycline‐induced cardiotoxicity, which is a model of accelerated heart aging. In conclusion, plasma elevation of ACBP/DBI constitutes a novel biomarker of chronological aging and facets of biological aging with a prognostic value in cardiovascular disease. Abstract : Montegut et al. provide evidence in favor of a proaging function of acyl CoA binding protein (ACBP) across multiple systems: yeast, mice and humans with cardiovascular disease.